(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2023)
This paper presents the results of the development of a model of the intersection using the PTV VISSIM simulation software. One of the problematic intersections in the city of Tashkent was selected and the traffic flow during peak hours was studied to analyze the intersection. The article discusses two solutions to reduce the amount of toxic gases and fuel consumption. The first solution is by optimizing the traffic light phases and changing their control cycle. The second solution represents a reduction by changing the geometric parameters of the intersection. After we applied both solutions, the service level of the intersection, LOS, increased from F to B.